ANALISIS PENGARUH COUNTRY OF ORIGIN DAN COLLECTIVISM TERHADAP PURCHASE INTENTION YANG DIMEDIASI OLEH CUSTOMER UNCERTAINTY - Syafira Khairani; Kurniawati Kurniawati (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This study aims to find out how much influence Country of Origin and Collectivism have on purchase intention mediated by customer uncertainty by using a case study on local shoes in Indonesia. This study uses a descriptive quantitative research method. In sampling the technique used is a non-probability sampling technique with purposive sampling. For data collection in this study using the technique of distributing questionnaires and collecting secondary data. To calculate the results of the questionnaire distribution, a Likert scale with an interval scale was used. This research model is using path analysis. With data analysis using AMOS. The results showed that Country of Origin and Collectivism had a positive effect on Purchase Intention. Meanwhile, Country of Origin has a negative effect on Purchase Intention with Customer uncertainty as mediation and Collectivism has a negative effect on Purchase Intention with Customer Uncertainty as mediation.